Treatment of Kawasaki disease with a moderate dose (1 g/kg) of intravenous immunoglobulin - Pongsak Khowsathit (2018)
Background: Kawasaki disease is an acute febrile illness recognized most often in young children. Coronary abnormality is the most serious complication preventable with intravenous immunoglobulin (IVIG) administration. Various treatment regimens of IVIG have been reported. Objective: To determine initial treatment failure and prevalence of coronary artery abnormality (CAA) in Kawasaki disease (KD) treated with a moderate dose (1 g/kg) of intravenous immunoglobulin (IVIG). Method: All patients with a diagnosis of KD who had initial treatment with 1 g/kg of IVIG at Ramathibodi Hospital between 1994 and 1998 were reviewed retrospectively. Results: Thirty-one of 41(76%) patients responded completely to a single treatment with a moderate dose of IVIG (group A). The second dose of 1 g/kg of IVIG was required in 7 patients (17%) due to persistent fever more than 48 hours after the initial treatment (group B), and 3 patients (7%) required 3 doses of 1 g/kg of IVIG due to persistent fever after the second dose (group C). During the convalescent phase, there were 19 per cent, 29 per cent and 100 per cent of the patients in group A, B and C, respectively who developed CAA with an overall rate of 27 per cent. After 1-year follow-up, the prevalence of CAA had decreased to 3 per cent, 0 per cent and 67 per cent in the according groups with overall rate of 9.6 per cent. Only 1 patient in group C developed a giant aneurysm of the right coronary artery. Conclusion: The efficacy of a moderate dose (1 g/kg) of IVIG in preventing CAA is lower than that of the high dose regimen (2 g/kg) reported previously. Short duration of fever before starting IVIG and low hemoglobin level may be the risk factors of unresponsiveness to moderatedose IVIG.